Democracy and COVID-19 Outcomes - Gokhan Karabulut; Klaus F. Zimmermann; Mehmet Huseyin Bilgin; Asli Cansin Doker (Global Labor Organization (GLO), 2021)
More democratic countries are often expected to fail at providing a fast, strong, and effective response when facing a crisis such as COVID-19. This could result in higher infections and more negative health effects, but hard evidence to prove this claim is missing for the new disease. Studying the association with five different democracy measures, this study shows that while the infection rates of the disease do indeed appear to be higher for more democratic countries so far, their observed case fatality rates are lower. There is also a negative association between case fatality rates and government attempts to censormedia. However, such censorship relates positively to the infection rate.
Keywords: D72; C30; P16; I19; 330; Democracy; COVID-19; Coronavirus; Pandemic; Lockdown; Media Censoring